Upaya Peningkatan Imun Lansia melalui Sleep Hygiene di Panti Sosial Tresna Werda Budi Luhur Jambi - Muhammad Hidayat; Hesty Hesty; Muhammad Azhari (Jurnal Abdimas Kesehatan (JAK), 2021)
One of the strategies to increase immunity in the elderly is that the need for sleep is fulfilled in quality and quantity so that it can improve the quality of life of the elderly. The best way to achieve quality and quantity sleep in the elderly is with sleep hygiene. Sleep hygiene is an exercise or habit that can affect sleep. Good sleep hygiene can prevent the development of sleep disorders. Sleep disorders experienced by a person indicate that there is poor sleep hygiene which is caused by a lack of knowledge of the elderly about sleep hygiene so that it has a negative impact on the elderly's immunity. This condition is experienced by the elderly who are in the transcendental social care institution. The tresna werda budi luhur social institution is a partner social institution that has implemented gerontik services according to the program, but in practice there are elderly people who experience poor sleep hygiene. One of the efforts that can be made by the community service implementation team is to provide health education to the elderly. The output of this community service activity is an effort to improve the immunity of the elderly through sleep hygiene. The implementation method used is survey, observation, interview, discussion, and demonstration through health education. This activity was carried out in 12 sessions, attended by 55 elderly people. The result of this activity is conducting health education and awakening the elderly to sleep hygiene and making media through the daily schedule of the elderly with the help of an alarm clock so that the final evaluation of the elderly begins to understand and be aware and able to independently of sleep hygiene. Sleep hygiene is monitored and continued by nurses on duty at the Tresna Wombat Social Home to become a sustainable program